The Nutritional content and organoleptic properties of foodbars with substitution of tofu dregs flour : Nutritional content, foodbar, tofu dregs flour, emergency food - Selvia, Cindy; Ratnayani (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2023)
Tofu pulp still has a relatively high protein content because in the process of making tofu not all protein content is extracted. This study aims to analyze nutritional content and organoleptic properties of foodbars. This experimental research design uses a completely Randomized Design (CRD) with three substitution levels including F1 (70% wheat flour and 30% tofu dregs flour), F2 (60% wheat flour and 40% tofu dregs flour), F3 (50% wheat flour and 50% tofu dregs flour), Data from organoleptic test results were analyzed using Kruskal Wallis test. The results of proximate were analyzed using independent t-test. The organoleptic analysis of the hedonic test showed that the selected foodbar formula was F1. The results of proximate analysis of selected foodbar contains 9.58% protein, 19.8% fat, 33.5% carbohydrate, 19.6% water, 1.37% ash, 14,7% fiber.